Window dressing systemic importance: Evidence from EU banks and the G-SIB framework - Luis Garcia; Ulf Lewrick; Taja Sečnik (European Banking Authority (EBA), 2021)
Building on previous research, we study banks' balance sheet year-end patterns in the European Union (EU) to assess the impact on supervisory measures of their systemic importance. We find that some global systemically important banks (G-SIBs) in the EU compress their balance sheet at year-end to an extent that it allows them to reduce their systemic importance, thus potentially mitigating the impact of the G-SIB capital surcharges or avoiding G-SIB designation altogether. Since some year-end adjustments are a common feature, we compare G-SIBs' adjustments to those of other systemically important institutions (O-SIIs) and observe that the compression of the latter banks' balance sheets is notably smaller. G-SIBs' balance sheets adjustments reflect several drivers, with the most notable year-end declines observed for intra-financial assets and liabilities as well as banks' notional amounts of over-the-counter derivatives. Reduction is most pronounced for G-SIBs characterised by comparatively high leverage. This evidence of possible window dressing underscores the importance of supervisory judgement in the assessment of G-SIBs, which is indeed a core component of the identification process. We also suggest greater use of average as opposed to point-in-time data in the quantitative part of the G-SIB identification process.
Keywords: G20; G21; G28; 330; Systemically important bank; systemic risk; regulation; financial stability